Analysis of Mimicry Language in Sabai Sunwoo's Novel as Teaching Material for Strengthening Global Diversity Character - Rahayu,; Mukti Widayati,; Nurnaningsih, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The purpose of this research is to analyze the mimicry language in the novel "Sabai Sunwoo" as teaching material for strengthening global diversity character. This study uses a qualitative descriptive approach and literary content analysis techniques. The research data consists of words and sentences related to mimicry language found in the novel "Sabai Sunwoo." These materials are intended to be used as teaching resources to enhance the depiction of characters with global diversity. The primary data source of this research is the novel titled "Sabai Sunwoo" by Akmal Nasery Basral. Data were collected through documentation procedures, as well as reading and note-taking approaches. The validity of the data was ensured using source triangulation and theory triangulation methods. The data analysis strategy employs a dialectical approach within the sociology of literature. According to the research findings, mimicry language in Akmal Nasery Basral's novel "Sabai Sunwoo" is prominently displayed through the life of the main character, Sabai Rangkayo Sunwoo. This mimicry reflects the cultural clash between Korea and Indonesia and encompasses three types: behavioral mimicry, language and food mimicry, and lifestyle mimicry. The novel "Sabai Sunwoo" is suitable for use as literary teaching material in high school because it meets the standards of validity and applicability. By meeting these standards, the novel not only serves as a valid and reliable source but can also be effectively implemented in the educational curriculum to support the achievement of learning objectives.